Plasma catalysis of carbon nanoparticles synthesis in the pyrolytic chamber - Veremii, Iu.P.; Iukhymenko, K.V.; Chernyak, V.Ya.; Liptuga, A.I.; Lisitchenko, T.E.; Demchina, V.P.; Kudryavzev, V.S. (Вопросы атомной науки и техники, 2012)
For experimental studies the generation of carbon nanoparticles with continuous removal of material was used plasmaliquid system with discharge in reverse vortex flow of "tornado" type. As a model of hydrocarbon has been used 96% ethanol. To generate reverse vortex flow used inert gas argon. The possibility of continuous transport of carbon nanomaterials from the synthesis area of solid-phase chemically passive microparticles revealed. Analysis of gas samples was carried out on gas chromatograph 6890N Agilen. Purified carbon samples investigated by Fourier spectrometer "Infralyum FT-801" Для исследования генерации наночастиц углерода с непрерывным удалением материала была использована плазменно-жидкостная система с обратновихревым потоком типа "торнадо". В качестве модельного углеводорода был использован 96% этанол. Для создания обратновихревого потока использовали инертный газ аргон. Выявлена возможность непрерывного удаления углеродных наноматериалов из области синтеза с помощью твердофазных химически пассивных микрочастиц. Анализ проб газа проводился на газовом хроматографе 6890N Agilen. Очищенные образцы углерода исследовали с помощью фурье-спектрометра "Инфралюм ФТ-801". Для дослідження генерації наночастинок вуглецю з безперервним видаленням матеріалу була використана плазмово-рідинна система зі зворотньовихровим потоком типу "торнадо". В якості модельного вуглеводню був використаний 96% етанол. Для створення зворотньовихрового потоку використовували інертний газ аргон. Виявлено можливість безперервного видалення вуглецевих наноматеріалів з області синтезу за допомогою твердофазних хімічно пасивних мікрочастинок. Аналіз проб газу проводився на газовому хроматографі 6890N Agilen. Очищені зразки вуглецю досліджували за допомогою фур'є-спектрометра "Інфралюм ФТ-801".